-12=-5-6x+11

Simple and best practice solution for -12=-5-6x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=-5-6x+11 equation:


Simplifying
-12 = -5 + -6x + 11

Reorder the terms:
-12 = -5 + 11 + -6x

Combine like terms: -5 + 11 = 6
-12 = 6 + -6x

Solving
-12 = 6 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-12 + 6x = 6 + -6x + 6x

Combine like terms: -6x + 6x = 0
-12 + 6x = 6 + 0
-12 + 6x = 6

Add '12' to each side of the equation.
-12 + 12 + 6x = 6 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 6 + 12
6x = 6 + 12

Combine like terms: 6 + 12 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| D+-8d+7=0 | | 2x+12+6x-10=180 | | -0.06y+0.08(1100-y)=0.36y | | 8x+12=9x+5 | | -5a-5(1-4a)=-5+4a | | 2(4+x)=4x+3 | | 5x-16=4x+7 | | 4x+3x=6x-6 | | 57=3y | | 3y+1=28 | | 5x-20=2x+4 | | 5d-2=63 | | -0.06y+0.08(1100-y)=0.36 | | 4x+3x=6x | | -3x+9=2x-6 | | 9n-12=69 | | 3y+14=5 | | -6x-17=-4x+7 | | 8(x+2)=3x+5 | | -11*3=15+-6*3 | | 7.8p-18=2.6p-5 | | 3x+8x-40=48 | | 9(x-5)=8(x-1) | | -96+5x=-8x+86 | | 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) | | 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= | | 28=(4+x)+x | | 178-5x=40x+18 |

Equations solver categories